2018
DOI: 10.1016/j.apsusc.2018.03.237
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring plasmonic response by Langmuir–Blodgett gold nanoparticle templating for the fabrication of SERS substrates

Abstract: Nanoparticle self-assembly is a robust and versatile strategy for the development of functional nanostructured materials, offering low-cost and scalable methods that can be fine-tuned for many different specific application. In this work, we demonstrate a pathway for the fabrication of tailorable quasi-two-dimensional lattices of gold nanoparticles to be used in Surface Enhanced Raman Scattering (SERS) detection of biomolecules. As a first step, nanoparticles are spread as a monolayer at the water/air interfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 30 publications
1
30
0
Order By: Relevance
“…In our previous work studying LB films prepared using commercial gold NPs of 10 nm [ 12 ], we estimated the size of the hotspots after different amounts of gold electroless plating was applied on the bare NP layer by comparing the UV–vis spectrum of our substrate with that of gold NP of different sizes, as reported by the NP manufacturer ( Figure 1 ). We found that, for the optimal electroless plating time (8–9 min), the average effective hotspot size was around 50 nm.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In our previous work studying LB films prepared using commercial gold NPs of 10 nm [ 12 ], we estimated the size of the hotspots after different amounts of gold electroless plating was applied on the bare NP layer by comparing the UV–vis spectrum of our substrate with that of gold NP of different sizes, as reported by the NP manufacturer ( Figure 1 ). We found that, for the optimal electroless plating time (8–9 min), the average effective hotspot size was around 50 nm.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, we used commercial spherical gold NPs of sizes 5–40 nm, and studied the performance of LB films prepared at different lateral pressures for each particle size. For the final SERS substrates, we increased the size and roughness of the hotspots by applying a common gold electroless plating time of 8 min, which was found to be near optimal in our previous study [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations